Strategic technology alliances, technology transfer and the performance of Malaysian manufacturer - Juhaini, Jabar (MTUN UTeM, 2012)
Organizations are realizing the strategic importance of technology alliances to enhance and maintain their competitive advantage. The turbulent business environment compels firms to adopt appropriate technologies for effective and efficient operations. While many firms are inclined to source external technology or form alliances, there are various considerations that can affect the success of such initiatives. This study examines the relationship between factors enabling strategic technology alliances (STAs), technology transfer and organizational performance. Based on three theories namely: Resource-based View (RBV); Organizational Learning Theory (OLT); and Technology Acceptance Model (TAM), this paper presents a model on the antecedent and outcomes of STA that is analyzed using structural equation modeling (SEM). The findings depict that absorptive capacity, type of alliances; relative advantage and perceived ease of technology implementation affect the alliance, which in turn determine organizational performance. Further tests show that technology transfer only partially mediates the relationship between STA and organizational performance. This research provides platforms and consideration for the implementation of new technologies and capabilities in manufacturing firms in a developing nation.